The racial contract - Mills, Charles W. 1951-2021 (Cornell University Press, 2022)
The Racial Contract puts classic Western social contract theory, deadpan, to extraordinary radical use. With a sweeping look at the European expansionism and racism of the last five hundred years, Charles W. Mills demonstrates how this peculiar and unacknowledged "contract" has shaped a system of global European domination: how it brings into existence "whites" and "non-whites," full persons and sub-persons, how it influences white moral theory and moral psychology; and how this system is imposed on non-whites through ideological conditioning and violence. The Racial Contract argues that the society we live in is a continuing white supremacist state.As this 25th anniversary edition—featuring a foreword by Tommy Shelbie and a new preface by the author—makes clear, the still-urgent The Racial Contract continues to inspire, provoke, and influence thinking about the intersection of the racist underpinnings of political philosophy